Strategi Biro Pemberitaan Parlemen DPR RI Menghadapi Berita Negatif di Media Massa - Yonarisman Muhammad Akbar; Raesita Rakhmawati Rosadi; Ida Royandiah; Mohamad Fajar Haqi Ismaya; Dina Fadiyah (Universitas Islam Darul Ulum Lamongan, 2023)
The House of Representatives of the Republic of Indonesia (DPR RI) plays a vital role and significant contribution in the areas of legislation, budgeting, and oversight. This institution is known as the